2020
DOI: 10.1029/2019sw002378
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Evolution of Different‐Scale Ionospheric Irregularities in Central and East Siberia During the 27–28 May 2017 Geomagnetic Storm

Abstract: We present a multi-instrumental study of ionospheric irregularities of different scales (from tens of centimeters to few kilometers) observed over the Central and East Siberia, Russia, during a moderate-to-strong geomagnetic storm on 27-28 May 2017. From high-frequency (HF) and ultrahigh-frequency (UHF) radar data, we observed an intense auroral backscatter developed right after the initial phase of the geomagnetic storm. Additionally, we examined variations of Global Positioning System (GPS)-based ROT (rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
5
0
1
Order By: Relevance
“…Based on these results, it becomes possible to use PC index instead of Newell's function in the OVATION-Prime precipitation model. The modified OVATION-Prime with PC application was already successfully used to study processes in the Earth's atmosphere in [34], where the multi-regression formula was taken to switch from N to PC index:…”
Section: Methodsmentioning
confidence: 99%
“…Based on these results, it becomes possible to use PC index instead of Newell's function in the OVATION-Prime precipitation model. The modified OVATION-Prime with PC application was already successfully used to study processes in the Earth's atmosphere in [34], where the multi-regression formula was taken to switch from N to PC index:…”
Section: Methodsmentioning
confidence: 99%
“…During geomagnetic storms, the enhanced ring current retards the onset of nightside reconnection and thus the onset of substorms, allowing the auroral oval to reach larger sizes prior to substorm expansion phase onset (Milan, 2009; Milan, Grocott, et al., 2009; Milan, Hutchinson, et al., 2009). Recently, it has been demonstrated that storm times are vital to understanding extreme GIC signatures (Smith et al., 2019, 2021), and work has been done to explore Birkeland currents during geomagnetic storms (e.g., Kleimenova et al., 2021; Lukianova, 2020a, 2020b; Maute et al., 2021; Ovodenko et al., 2020; Pedersen et al., 2021, 2022, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…During geomagnetic storms, the enhanced ring current retards the onset of nightside reconnection and thus the onset of substorms, allowing the auroral oval to reach larger sizes prior to substorm expansion phase onset (Milan, 2009;Milan, Grocott, et al, 2009;Milan, Hutchinson, et al, 2009). Recently, it has been demonstrated that storm times are vital to understanding extreme GIC signatures (Smith et al, 2019(Smith et al, , 2021, and work has been done to explore Birkeland currents during geomagnetic storms (e.g., Kleimenova et al, 2021;Lukianova, 2020aLukianova, , 2020bMaute et al, 2021;Ovodenko et al, 2020;Pedersen et al, 2021Pedersen et al, , 2022Pedersen et al, , 2023. Hutchinson et al (2011) developed a method to algorithmically identify the individual phases (initial, main, and recovery phases) of geomagnetic storms, finding that the duration of the main phase increased with storm intensity up to a point but then started to decrease again, which they argued was contrary to Yokoyama and Kamide (1997).…”
mentioning
confidence: 99%
“…In this investigation, we present and discuss in detail the ionospheric impact in the South American sector produced by the intense geomagnetic storm that occurred in May 2017. The effects of this geomagnetic storm was already investigated in other sectors, such as over North America by Jonah et al (2018) that using GPS observations, reported the presence of both equatorward propagating large scale traveling ionospheric disturbances (TIDs) and poleward propagating medium scale TIDs, over Europe by Pezzopane et al (2019) that using data from the WIND spacecraft, from the GOES and THEMIS satellites, INTERMAGNET magnetometer array, and GPS receivers, investigated the effects on magnetosphere-plasmasphere-ionosphere system, over Central and East Siberia by Ovodenko et al (2020) that presented a muti-instrumental study of ionospheric irregularities of different scales from tens of centimeters to few kilometers, and over Asian sector by Liu et al (2020) that using multi-instrumental observations, including GNSS-TEC and other complementary datasets, investigated the multi-scale ionospheric responses. For the present investigation, latitudinal/longitudinal VTEC differences from selected GPS stations were used in orther to evaluate the ionospheric response to the geomagnetic storm at different chains over the South American sector.…”
Section: Introductionmentioning
confidence: 99%